2021
DOI: 10.1210/clinem/dgab482
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surgically Curable Primary Aldosteronism by Imaging in a Large, Multiethnic International Study

Abstract: Context Adrenal glands imaging is recommended by the current guidelines for the work-up of primary aldosteronism (PA). However, its diagnostic performance has not been established in large multi-ethnic cohorts of patients submitted to adrenal vein sampling (AVS) and adrenalectomy. Objective To assess the diagnostic accuracy of cross-sectional adrenal imaging. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Altogether, this means errors in 18% and 3% of lateralization diagnostics with the 11 C‐MTO‐PET and AVS methods, respectively, among those eligible for adrenal surgery. In comparison, based on analysis of more than 1300 imaging studies in a recent report, anatomical imaging‐based lateralization would have excluded surgical treatment from 22% of the subjects and resulted in the removal of the non‐culprit adrenal gland from 6% of the subjects 13 . Previous studies have shown a 36%–39% probability of errors in operation side selection based on adrenal CT, but these numbers included those diagnosed with bilateral disease 27–30 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Altogether, this means errors in 18% and 3% of lateralization diagnostics with the 11 C‐MTO‐PET and AVS methods, respectively, among those eligible for adrenal surgery. In comparison, based on analysis of more than 1300 imaging studies in a recent report, anatomical imaging‐based lateralization would have excluded surgical treatment from 22% of the subjects and resulted in the removal of the non‐culprit adrenal gland from 6% of the subjects 13 . Previous studies have shown a 36%–39% probability of errors in operation side selection based on adrenal CT, but these numbers included those diagnosed with bilateral disease 27–30 …”
Section: Discussionmentioning
confidence: 99%
“…1300 imaging studies in a recent report, anatomical imaging-based lateralization would have excluded surgical treatment from 22% of the subjects and resulted in the removal of the non-culprit adrenal gland from 6% of the subjects. 13 Previous studies have shown a 36%-39% probability of errors in operation side selection based on adrenal CT, but these numbers included those diagnosed with bilateral disease. [27][28][29][30] Despite great expectations, the use of 11 17 However, the ability of 11 C-MTO-PET to diagnose unilateral non-classic forms of PA that are becoming more prevalent remains unanswered by these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, AVS is available at limited institutions, therefore, efforts have been made to identify cases in which AVS can be bypassed and to determine the indications for surgery by CT scan [ 27 , 28 , 29 , 30 ]. It should be noted, however, that the results of CT imaging and AVS differ in 28–38% of cases [ 31 , 32 ]. Thus, AVS has been recommended for precise subtype diagnosis to date.…”
Section: Introductionmentioning
confidence: 99%